The effect of human capital, market orientation, and digital marketing technology on business performance in optical SMEs in East Java - Pratama, M Adhitya Nugraha; Harti, Harti; Hariyati, Hariyati (Technium Social Sciences Journal, 2021)
This study aims to determine the effect of human capital, market orientation, and digital marketing technology on business performance in optics SMES in East Java. The type of this study used is descriptive study with a quantitative approach. The population in this study were the owners of optics SMES scattered in East Java with a sample of 96 respondents. The data collection techniques used in this study is questionnaires, documents. The data analysis technique used is multiple linear regression analysis using SPSS 26ver. The findings found that each of the independent variables included in this study human capital, market orientation, and digital marketing technology partially or simultaneously have positive and significant effect on business performance in optics SMES in East Java.